Impact of the acceleration voltage on the processing of γ-TiAl via electron beam powder bed fusion - Reith, M.; Franke, M.; Körner, Carolin (Progress in Additive Manufacturing, 2023)
Electron beam powder bed fusion (PBF-EB) is an additive manufacturing (AM) technology that is maturing toward broader industrial applications. However, conventional PBF-EB machines are still limited to 60 kV acceleration voltage (Ub). Therefore, this work presents the first results of a novel prototype PBF-EB machine capable of acceleration voltages up to 150 kV. In general, a higher acceleration voltage enables larger beam powers, which shortens the pre-heating time and makes a larger pre-heating area available. Moreover, a lower beam current is required for the same power during pre-heating, enabling the processing of a gamma titanium aluminide (γ-TiAl) alloy without any process gas. γ-TiAl cuboids are built in a vacuum atmosphere (2×10–5 mbar) with 60 , 125 , and 150 kV acceleration voltage. Additionally, the deeper penetration of higher acceleration voltage should be beneficial for melting as well. Cuboids are examined for defects and aluminum content to show the influence of the acceleration voltage on the process window, melt pool formation, gas porosity, and aluminum evaporation. In short, this work aims to investigate the impact of a higher acceleration voltage on the whole PBF-EB process.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Acceleration voltage; Additive manufacturing; Beam diameter; Electron beam powder bed fusion; Process window; Titanium aluminide